BEN - GIBEN DAN NASEâ LANCENG PERNIKAHAN DI DALEMAN GALIS BANGKALAN MADURA PERSPEKTIF HUKUM ISLAM - SyafiÃ¢Â€Â™ie, Moh. Toyyib (Program Studi Hukum Keluarga Islam Fakultas Syariah dan Hukum, 2013)
Abstract : This is a field research to answer the two fundamental questions, namely: what the status of the ben-giben and naseâ lanceng tradition related to marital contract in village Daleman, district Galis, region Bangkalan-Madura is, and how the point of view of the Islamic law to their legal status is. The data of the research are gained through interview to some of the villageâs local religious figures and the participants of the ben-giben and naseâ lanceng. The collected data are then qualitatively analyzed by using a descriptive technique and inductive-deductive mindset. The study concludes that: first, the handing of the ben-giben and naseâ lanceng is that if the parents want to marry their child, they have to include the items required in the form of cattle, samper lasem, a basket of egg and a cone; second, the tradition of ben-giben and naseâ lanceng is not contrary to Islamic law and to the principle of marriage, namely the principle of willingness between the groom and the bride. Based on the above conclusions, the author recommends that such tradition may be continued and preserved to the next generation of the village. In addition, a belief about a negative impact of the tradition for the natives is necessarily clarified by the local religious figures since it is naturally happening under the Godâs will. Keywords : Ben-Giben, Naseâ Lanceng, Grant, Charity, Habit.